2012
DOI: 10.5539/ijef.v4n2p163
|View full text |Cite
|
Sign up to set email alerts
|

Interest Rate Pass-Through and Monetary Transmission in Asia

Abstract: This study seeks to examine the effectiveness of interest rates transmission mechanism from money market rate into retail banking rate in several Asian countries. In particular, we intend to investigate the differences in the degree of pass-through from monetary policy rate into deposit and lending rates across countries and between the pre-and post-crisis of 1997. The study is carried out by running the Seemingly Unrelated Regression (SUR) equations. The results suggest that the transmission rate from money m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 13 publications
3
22
0
2
Order By: Relevance
“…This finding is consistent with the observation of Bruna (2008) who pointed out that deposit rate reacts quicker than the lending rate to the change of the money market rate. The work of Tai et al (2012) and Tang et al (2015) also reported that the deposit rate has a higher degree of pass-through than the lending rate. Our results further show that the U.S. federal funds rate is found to have an impact on the lending rate but not on the deposit rate.…”
Section: Resultsmentioning
confidence: 95%
“…This finding is consistent with the observation of Bruna (2008) who pointed out that deposit rate reacts quicker than the lending rate to the change of the money market rate. The work of Tai et al (2012) and Tang et al (2015) also reported that the deposit rate has a higher degree of pass-through than the lending rate. Our results further show that the U.S. federal funds rate is found to have an impact on the lending rate but not on the deposit rate.…”
Section: Resultsmentioning
confidence: 95%
“…Tai, Sek and Har (2012) explored the effectiveness of interest rate transmission mechanism in six Asian economies (Note 7) using Seemingly Unrelated Regression (SUR) model for the period 1988-2010 (Note 8). The study found an evidence of slow and sluggish transmission across the countries, high degree of interest rate stickiness or failure of government in controlling the market rate is the possible factors for the slow and small transmission into deposit and lending rates.…”
Section: Overview Of the Literaturementioning
confidence: 99%
“…The model assumes perfect competition with complete information and equality of prices with marginal costs. Likewise, the derivative of prices with respect to marginal cost equals one but becomes less than one if the perfect competition and information prices are suspended (Tai, Sek, & Har, 2012;Rousseas 1985).…”
Section: Model Specificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the studies indicated several characteristics such as the size of the bank, structure of the financial market, type of customers, competitiveness of the banking sector, elasticity of the demand on banking services and information asymmetry in the economy and the loan risk level that makes stickiness of interest rate pass-through in the short-run. Also, a cross country study to assess retail rate stickiness was conducted for Asia by Tai, Sek and Har (2012). This study consists of two periods: before the Asian financial crisis and after the financial crisis.…”
Section: Incompletenessmentioning
confidence: 99%